Upgrading a Water Cooling System with Flushing Possibilities - Valentino Stojkovski, Viktor Iliev, Filip Stojkovski (My University, 2021)
This paper presents an analysis of the operating parameters of a water cooling system of the structural part of a furnace for rolling mills preparation. The structural solution of the cooling system is performed as flow, with a constant inflow of fresh water and drainage from the system. Four longitudinal pipes are installed, which are supported by vertical girders. Vertical girders should provide thermal stability to ensure pipe-plate horizontality. The vertical girders are regularly connected to the cooling system by placing pipes direct into the vertical girder, which engages the part of the water supply that cools the vertical girder, and the same water is returned to the cooling system and continuously transferred to the next girder. During operation, due to the quality of cooling water that is not chemically treated, calcium carbonate is formed; the presented impurities clog the flow channels of the cooling system in the vertical girders. The application of CFD analysis reveals the conditions of water flow in the cooling system of vertical girders. From the analysis of the obtained results, it is proposed to upgrade the existing system by installing a flushing system, which will ensure a directed and controlled inflow in the zones of the cooling system. The conceptual solution for the flushing system and the effects of its operation are given in this paper.
Keywords: cooling system, CFD analyses, flushing system